A Pilot Study: Promoting Understanding and Peer Success (PUPS) in the Campus Community - Laura Pruitt Walker; Kimberly D. Helms (The Ohio State University Libraries, 2018)
Background: Suicide is one of the leading causes of death in the United States and is escalating in some populations, such as college students. Suicide is the 2nd leading cause of death among college students (Caruso, 2018). The number one cause of suicide is depression (Caruso, 2018). Aim: The aim of the Promoting Understanding and Peer Success (PUPS) project is to explore innovative approaches to teaching and learning in a psychiatric mental health course and to provide early identification and intervention for students or staff who are identified as "at risk" for suicide, depression, anxiety, and substance abuse. Methods: Researchers are utilizing a qualitative approach when collecting data from nursing students involved in this study. The Nursing Students are asked to engage in focus group interview questions and to complete a self-reflection activity focused on the PUPS project. Results: Nursing students have conducted suicide, depression, anxiety and substance abuse screenings on approximately 500 campus student and staff participants thus far. Many of these screenings have resulted in distribution of educational resources, referral and follow up with counseling services. Conclusions: Researchers are continuing to collect data in the form of focused group interview questions, anecdotal comments, and end of the term course evaluations from the nursing students. Thematic coding is pending. Based upon anecdotal comments from the nursing students, the course faculty/researchers of this study believe the PUPS Project is successful.